Health-Promoting Leadership: Concept, Measurement, and Research Framework - Yao, Lei; Li, Ping; Wildy, Helen (Frontiers in Psychology, 2021)
Employee health is not only positively related to the employee well-being and family happiness, but also impacts organizations, and society as a whole. We searched the health-promoting leadership literature in the following databases: Web of Science, ProQuest, EBSCO, and a Chinese local database. Based on this research, we clarify the concept of health-promoting leadership, propose a definition of health-promoting leadership, and examine measurement scales for this type of leadership. We also suggest a research framework for health-promoting leadership, demonstrating its potential outcomes at both the individual level (e.g., health, well-being, job attitudes) and the organizational level (e.g., health management culture and practices); the mechanisms for its development based on conservation of resources theory, the job demands–resources model, social learning theory, and social exchange theory; and antecedents (e.g., health values, health awareness, organizational health culture, organizational health climate, and organizational health promotion behavior control). Finally, we identify six potential research areas: Research level, performance, the impacts of health-promoting leaders on themselves, moderators, research methods, and intervention effects on health-promoting leadership.